La emision de series radiales basadas en cuentos y leyendas de la ciudad de Loja en radio Universitaria 98.5 fm para el desarrollo del imaginario infantil. Período septiembre 2012-agosto 2013. Propuesta alternativa - Fajardo Montaño, Carla Guillermina (2016)
The present research was conducted in the city of Loja, in order to know the importance of a space committed to promote interest in stories and legends of the city of Loja dedicated to children so that in this way the tradition remains in the memory of those who listen to the series. Here it was also used the voice as a narration instrument for creating an environment according to the story or legend and so take the audience to imagine the scenes in which the narration is being developed. Here it was very important to use methods such as deductive, inductive and scientific method, as well as field observation techniques and bibliography. Furthermore, it was also used the survey which served to support conclusions, recommendations, and proposal. In this investigation, reliable results that allowed to reach the following conclusions were obtained: Radio Universitaria 98.5 FM does not dedicate a space to the child population areas. Most respondents have little ones at home who may be interested in the proposal. Surveyed people also believe it is very important to know our culture in terms of stories and legends of our city, and even more that children can imagine how it was before our city by those legends that our relatives told us. And on recommendations, it was proposed the implementation of a radio series that catches attention of children through advances of their interest that are innovative and attention grabbing, and the use of different tones of voice during the transmission to take each child to that year, at that moment in which the story or legend happens